Physician management of moderate-to-severe acute pain: Results from the Physicians Partnering Against Pain (P3) Study - McCarberg, MD, Bill H.; Patel, PharmD, MBA, Aarti A.; Benson, MS, Carmela J.; Mody, PharmD, MBA, Samir H.; Chow, PharmD, MPH, Wing; Zema, PhD, Carla L.; Vorsanger, PhD, MD, Gary J.; Kim, PhD, MBA, MA, Myoung S. (Journal of Opioid Management, 2013)
Objective: To evaluate differences among physician specialties in the management of acute pain including prescribing practices and management of opioid-related side effects. Design and participants: The Physicians Partnering Against Pain (P3) survey was a nationwide study of US physicians and their patients with severe to moderate acute pain (<3 months). Main measures: Physicians were surveyed about volume of patients with moderate-to-severe acute pain in their practice, frequency of prescribing opioid analgesics, percentage of these patients returning for a follow-up visit after treatment, reasons patients discontinue treatment, frequency of recommending or prescribing treatment for opioid-related gastrointestinal (GI) side effects, and frequency of patients taking opioid analgesics that take additional treatments to manage GI side effects. Results: The 5,982 participating physicians represented primary care physicians (PCPs; 52 percent), pain specialists (25 percent), and other specialists (23 percent). PCPs and other specialists were less likely than pain specialists to prescribe opioid analgesics to patients (25.8 percent, 29.5 percent, and 44.8 percent, respectively). The vast majority of pain specialists (78 percent) also indicated that more than three quarters of their patients returned for a follow-up visit compared with only 40 percent of PCPs and 65 percent of other specialists. When ranking the reasons why they think patients discontinue opioid analgesics, pain specialists ranked unacceptable side effects higher than PCPs and other specialists. PCPs and pain specialists were more likely than other specialists to recommend or prescribe treatments to manage opioid-related side effects, such as nausea, vomiting, and constipation (38.3 percent, 38.5 percent, and 23.1 percent, respectively). Conclusion: The P3 Study confirms the challenge of pain management while balancing tolerability of opioid treatments from the physician perspective.